1984
DOI: 10.1159/000121311
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Somatosensory Input by Afferent and Efferent Neurons in the Vestibular Nerve of the Frog

Abstract: In the frog, we have recorded the activity of efferent and afferent fibers in the nerve of the horizontal semicircular canal in response to somatosensory stimulation. Recordings were made extracellularly by means of glass micropipettes filled with 2 M NaCl, and somatosensory stimulation was produced either by electrical stimulation of the sciatic nerve (ipsi- or contralateral to the recording side) or by vibratory stimulation of the gastrocnemius. The discharge frequency of 43 % of the efferent fibers recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Although, this study implicates the EVN in mediating changes to contralateral vestibular nuclei interactions that occur at the level of peripheral sensors, the classification of recorded neurons was not conclusive (for example, retrograde staining of recorded neurons was not performed to confirm their locations), and therefore provides a caveat to their results. However, in addition to canal stimulation, a significant increase in the discharge rate of 40% of peripheral efferent fibers was observed in response to sciatic nerve stimulation in the frog (Caston and Bricout-Berthout, 1984 ), suggesting that the function of the EVN may be linked to the spinal circuits underlying locomotion, a potential functional role elaborated further in Section The EVS Signals Corollary Discharge between Vestibular and Other CNS Structures.…”
Section: Physiology Of Evn Neuronsmentioning
confidence: 99%
“…Although, this study implicates the EVN in mediating changes to contralateral vestibular nuclei interactions that occur at the level of peripheral sensors, the classification of recorded neurons was not conclusive (for example, retrograde staining of recorded neurons was not performed to confirm their locations), and therefore provides a caveat to their results. However, in addition to canal stimulation, a significant increase in the discharge rate of 40% of peripheral efferent fibers was observed in response to sciatic nerve stimulation in the frog (Caston and Bricout-Berthout, 1984 ), suggesting that the function of the EVN may be linked to the spinal circuits underlying locomotion, a potential functional role elaborated further in Section The EVS Signals Corollary Discharge between Vestibular and Other CNS Structures.…”
Section: Physiology Of Evn Neuronsmentioning
confidence: 99%
“…Classic studies in fish ( Figure 2A ) demonstrated that somatosensory stimulation activates individual vestibular afferents ( Hartmann and Klinke, 1980 ; Highstein and Baker, 1985 ), and that visual stimulation can evoke directionally sensitive responses ( Klinke, 1970 ). Likewise, somatosensory and visual stimulation has also been reported to alter the firing activity of individual vestibular afferents in amphibians ( Figure 2B ; frog: Caston and Bricout-Berthout, 1982 , 1984 , respectively). Yet, in this latter vertebrate class, somatosensory stimulation can both inhibit and excite afferents, and thus contrasts with what is seen in fish.…”
Section: Introductionmentioning
confidence: 74%
“…The findings of prior investigations in frog had suggested that extravestibular signals (e.g., somatosensory, proprioceptive, and/or motor efference copy signals) transmitted through efferent neurons can be used to change afferent responses under specific behavioral conditions (Bricout-Berthout et al 1984; Caston and Bricout-Berthout 1984; Precht et al 1971; Schmidt 1963). Thus, we also tested this possibility by characterizing afferent responses to such extravestibular signals during passive stimulation of neck somatosensory and proprioceptive inputs, as well as during active head movements during which a command to move the head was produced (Sadeghi et al 2007).…”
Section: Results and Interpretationsmentioning
confidence: 99%